OPTIMIZING SOYBEAN GROWTH AND YIELD THROUGH ENHANCEMENTS WITH DECANTER CAKE AND PLANT GROWTH-PROMOTING RHIZOBACTERIA - Duaja, Made Deviani; Kartika, Elis; Buhaira, Buhaira; Wulandari, Ismi Barica Icha (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
Soybean (Glycine max (L.) Merril) is a food and industrial crop and a base for agricultural production. Adding organic material can increase plant growth and produce high yields. One of the organic materials that can be used is palm oil mill solid waste, specifically solid decanter cake (DC). However, the results showed that DC could only substitute 50 per cent of chemical fertilisers. DC must be combined with other materials, specifically Plant Growth plant-promoting rhizobacteria (PGPR), to maximise its benefits. PGPR is a group of bacteria that live in the plant rhizosphere and actively function as biofertilisers, biostimulants, and bioprotectants. Combining DC and PGPR is necessary because they have a mutually beneficial relationship, as DC is an organic material that can provide the nutrients PGPR bacteria need. This research will evaluate whether the collaboration of DC and PGPR can increase soybean growth and yield in ultisols using a Randomized Block Design. Combining decanter cake (DC) with a PGPR concentration can enhance soybean growth and yield. Soybean plants treated with 15-ton ha-1 + 50% PGPR DC tend to have the highest number of leaves, plant height, and number of branches, but DC 10-ton, ha-1 + 30% PGPR, has an equivalent effect. The treatment of 10 tons per hectare of decanter cake with 30% PGPR concentration tended to have the highest number of pods and yield.